NEW BUSINESS MODELS – Sustainability as a main focus - Pekki, Anton (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2015)
A business model is a structure frame of an organization that can bring significant benefits and competitive advantage when structured properly. The aim of this paper was to observe and describe development of business models’ and identify factors and elements of a business model that are in a key role from the perspective of an organizational sustainability. One is striving to bring out in this thesis how should truly sustainable business model look like and what are main characteristics of it. Additionally, some recommendations that could be helpful in order to build sustainable and balanced business model in a company are presented in this work. The meaning was to make theoretical and in some extent practical acquaintance with such new business models as open business model and sustainable business model. Long-term sustainability achievement in a company was in a centric role and used as a main criteria when constructing sustainable business model structure. The main research question in this study aims to answer: What a firm should consider in order to develop profitable and sustainable business model? This study is qualitative in nature and it was conducted using content analyze as a main method of this research. The perspective of the target data in this study is an outlook of its producers of how sustainability is reached in an organization throw business model and which practices are important and has to be taken into account. The material was gathered mainly from secondary sources and the theoretical framework was outright built based on secondary data. The secondary data that have been mostly dissertations, academic writings, cases, academic journals and academic books have been analyzed from the point of view of sustainability perspective. As a result it became evident that a structure of a business model and its implementation along with a strategy is often what leads companies to success. However, for the most part, overall business environment decides and delimits how the most optimal business model should be constructed in order to be effective and sustainable. The evaluation of key factors and elements in business model leading organization to sustainability should be examined throw triple bottom line perspective, where key dimensions are environmental, social and economic. It was concluded that dimensions should be evaluated as equal in order to attain total long lasting sustainability, contradicting traditional perspective in business where profit production is seen as only main goal of a business.

Liiketoimintamalli on organisaation struktuurikehikko, joka voi tuoda merkittäviä hyötyjä ja kilpailuedun kun se on rakennettu oikein. Tämän tutkielman tarkoituksena oli tutkia ja kuvata liiketoimintamalleja ja identifioida tekijät ja elementit liiketoimintamallista, jotka ovat keskeisessä roolissa organisaation kestävyyden näkökulmasta. Tutkielmassa pyritään tuomaan esille miltä kestävän liiketoimintamallin pitäisi näyttää ja mitkä ovat sen pääominaispiirteitä. Lisäksi tässä työssä on esitetty joitakin suosituksia, jotka voisivat auttaa rakentamaan kestävää ja tasapainotettua liiketoimintamallia. Tarkoituksena oli tutustua teoreettisesti ja jossain määrin praktiselta kannalta sellaisiin uusiin liiketoimintamalleihin, kuin avoimet ja kestävät liiketoimintamallit. Pitkän tähtäimen kestävyyden tavoittelu yrityksessä oli keskeisessä roolissa ja sitä käytettiin pääkriteerina kestävän liiketoimintamallin struktuuria rakentaessa. Tämän tutkimuksen pääkysymys pyrkii vastaamaan: Mitä yrityksen tulee huomioida kehittääkseen kannattavan ja kestävän liiketoimintamallin? Tämän tutkimuksen luonne on kvalitatiivinen ja se on suoritettu käyttämällä sisällönanalyysiä päätutkimusmetodina. Datan lähestymisnäkökulma tässä tutkimuksessa on sen tuottajien näkemys siitä, miten kestävyys saavutetaan organisaatiossa liiketoimintamallin avulla ja mitkä käytännöt ovat tärkeitä ja on otettava huomioon. Materiaali oli pääosin kerätty sekundaarilähteistä ja teoreettinen kehys oli rakennettu kokonaan sekundaarilähteiden pohjata. Sekundaaridata, joka on ollut suurimmaksi osaksi tutkielmia, akateemisia tekstejä, tapaustutkimuksia , akateemisia aikakausijulkaisuja ja akateemisia kirjoja on analysoitu kestävyyden näkökannalta. Tuloksena selvisi, että liiketoimintamallin struktuuri ja sen soveltaminen strategian kanssa on usein asia, joka johtaa yrityksiä menestymiseen. Suurimmaksi osaksi kuitenkin kokonaisvaltainen liiketoimintaympäristö määrää ja rajaa miten mahdollisimman optimaalinen liiketoimintamallin kokonaisuus rakennetaan saavuttaakseen tehokkuuden ja kestävyyden. Liiketoimintamallin päätekijöiden ja elementtien, jotka johtavat yrityksen kestävyyteen, arviointi on tehtävä kolmen ulottuvuuden näkökulmasta, jossa ulottuvuuksina ovat taloudellinen, yhteiskunnallinen ja ekologinen. On tultu päätökseen, että nämä ulottuvuudet on otettava huomioon tasapuolisesti, saavuttaakseen kestävyyden pitkällä aikavälillä. Tämä on ristiriidassa traditionalisen ajattelutavan kanssa, jossa tuloksen tuottaminen nähdään yrityksen ainoan päätavoitteena.